Yeast flocculation: a new method for characterising cell surface interactions - Azeredo, Joana (1997)
Flocculation is a property of yeast cells that has been traditionally used in industrial fermentations, especially in the brewing and wine industries. It is a cell wall interaction and an increase in flocculation is strongly correlated with an increase in cell surface hydrophobicity. Methods to assay yeast cell surface hydrophobicity are only qualitative and while electrostatic interactions can play an important role, they are not always taken into account. In this work, a simple and accurate method based on contact angle measurements is described to determine yeast cell surface hydrophobicity. With this method, it is possible to quantify yeast cell surface hydrophobicity by determining the free energy of interaction between cells and water molecules. Several yeast strains with different flocculation characteristics have been used to validate the method.